The Use of Tick Salivary Proteins as Novel Therapeutics - Chmelař, Jindřich; Kotál, Jan; Kovaříková, Anna; Kotsyfakis, Michail (Frontiers in Physiology, 2019)
The last three decades of research into tick salivary components has revealed several proteins with important pharmacological and immunological activities. Two primary interests have driven research into tick salivary secretions: the search for suitable pathogen transmission blocking or “anti-tick” vaccine candidates and the search for novel therapeutics derived from tick salivary components. Intensive basic research in the field of tick salivary gland transcriptomics and proteomics has identified several major protein families that play important roles in tick feeding and overcoming vertebrate anti-tick responses. Moreover, these families contain members with unrealized therapeutic potential. Here we review the major tick salivary protein families exploitable in medical applications such as immunomodulation, inhibition of hemostasis, and inflammation. Moreover, we discuss the potential, opportunities, and challenges in searching for novel tick-derived drugs.